Exploring Visual Culture Definitions, Concepts, Contexts - Rampley, Matthew (Edinburgh University Press, 2022)
An introduction to the study of visual culture, this book offers a view of 'visual culture' that includes not only images, but also other visual media and forms of expression, from architecture to fashion, design and the human body. The book is organised around three broad themes, exploring key ideas and debates that have occurred during the last 20 or so years:the meanings of the term 'visual culture' and of the various practices that form its basis conceptual approaches to the contemporary analysis of visual culture the cultural, social and historical contexts informing its production, distribution and consumptionDrawing on a wide range of examples from the last 100 years, the book adopts a cross-disciplinary perspective; it also explores, however, the limits of visual culture as an interdisciplinary field of study, engaging in current debates about the uses and value of the study of visual culture. It will therefore be of value both for readers new to the subject and also for those seeking fresh interventions into contemporary discussions within the field.Key FeaturesAccessibly written by a team of experts in the field Illustrated throughout Includes chapters on a wide range of visual forms, including architecture and urban design, film, crafts, fashion, design, fine art and the media